THE EFFECT OF WORK OVERLOAD AND THE WORK ENVIRONMENT PERFORMANCE EMPLOYEE IN PT TAKABEYA PERKASA GROUP - Alfira Seroja; Andi Saputra; Faryani; Syarfia A Rahman; Zainuddin Iba (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The aim of this research is to determine the effect of work overload and work environment on employee performance at PT Takabeya Mighty Group. This research is quantitative research with a total of 63 respondents and the sampling technique uses the Slovin formula because the population is more than 100. The data collection technique is carried out by distributing questionnaires. The analysis technique used in the research uses multiple linear regression analysis with the help of SPSS version 25 for Windows. The results of this research shows that partially the work overload does not have a significant effect on employee performance with a regression coefficient of = 0.619<2.0003. the work environment has a positive and significant effect on employee performance with a coefficient of = 4.133>2.0003.